1994
DOI: 10.1088/0741-3335/36/7a/027
|View full text |Cite
|
Sign up to set email alerts
|

Formation of internal and edge transport barriers in JT-60U

Abstract: Spontaneous formation of intemal transport barrier was observed in JT-60U high-& discharges, where q=3 surface is the most likely explanation for its radial location. Further improved confinement was brought about by the subsequent transition to the edge nansport barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…A growth rate γ of the n = 1 mode is about 430 s -1 in the early phase and is about 1,020 s -1 at t ≈ 6.322 s. Since the estimated τ w of the JT-60U vacuum vessel is ≈ 10 ms, the growth rate of 430 s -1 corresponds to ≈ 4 τ w -1 . Toroidal rotation velocity of the ohmic discharges is nearly zero within the uncertainty of the measurement by a charge-exchange recombination spectroscopy (CXRS) [21]. The diamagnetic drift is a dominant fluid drift in the poloidal direction in such ohmic discharges and its velocity is typically ≈ 5 km/s.…”
Section: Rwms Associated With Current-driven Kink Modesmentioning
confidence: 95%
“…A growth rate γ of the n = 1 mode is about 430 s -1 in the early phase and is about 1,020 s -1 at t ≈ 6.322 s. Since the estimated τ w of the JT-60U vacuum vessel is ≈ 10 ms, the growth rate of 430 s -1 corresponds to ≈ 4 τ w -1 . Toroidal rotation velocity of the ohmic discharges is nearly zero within the uncertainty of the measurement by a charge-exchange recombination spectroscopy (CXRS) [21]. The diamagnetic drift is a dominant fluid drift in the poloidal direction in such ohmic discharges and its velocity is typically ≈ 5 km/s.…”
Section: Rwms Associated With Current-driven Kink Modesmentioning
confidence: 95%
“…Figure 10 (a) shows a close correlation of ∆W ELM /W ped with a v T,ped under a P SEP ∼ 5-6 MW at each configuration, showing similar slopes in the dependence of ∆W ELM /W ped on v T,ped . A reason for the narrower dynamic range toward the co-direction in the v T,ped for the larger volume configuration is due to an offset toroidal rotation towards the counter-direction at the plasma's edge region due to larger losses of fast ions from perpendicular NBI [11][12][13]. As shown in Fig.…”
Section: Effects Of Toroidal Field Ripple On Elmsmentioning
confidence: 93%
“…discharge at a given P SEP as shown in Fig. 8, which is related to the losses of fast ions due to perpendicular NBI and the formation of negative E r [11,12]. From the results described above, it 005-4 is suggested that the effect of the resultant toroidal rotation at the plasma edge caused by the losses of the fast ions due to the TF-ripple on ELMs is also an interesting edge phenomenon, which may also provide a controllable parameter for ELM mitigation.…”
Section: Effects Of Toroidal Field Ripple On Elmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion temperature profiles, T i , were measured by charge-exchange recombination spectroscopy (CXRS) of carbon [27]. The effective charge number, Z eff , was estimated using visible bremsstrahlung, and its profile was assumed to be spatially uniform so that these values were capable of reproducing the measured neutron emission rate, S n [28].…”
Section: Experiments Of High-triangularity Elmy H-modementioning
confidence: 99%